The molecular assessment of SARS-CoV-2 Nucleocapsid Phosphoprotein variants among Indian isolates. Issue 2 (February 2021) - Azad, Gajendra Kumar
Abstract: Coronavirus disease- 2019 (COVID-19) has rapidly become a major threat to humans due to its high infection rate and deaths caused worldwide. This disease is caused by an RNA virus, Severe Acquired Respiratory Syndrome –Corona Virus-2 (SARS-CoV-2). This class of viruses have a high rate of mutation than DNA viruses that enables them to adapt and also evade host immune system. Here, we compared the first known Nucleocapsid Phosphoprotein (N protein) sequence of SARS-CoV-2 from China with the sequences from Indian COVID-19 patients to understand, if this virus is also mutating, as it is spreading to new locations. Our data revealed twenty mutations present among Indian isolates. Out of these, mutation at six positions led to changes in the secondary structure of N protein. Further, we also show that these mutations are primarily destabilising the protein structure. The candidate mutations identified in this study may help to speed up the understanding of variations occurring in SARS-CoV-2. Abstract : COVID-19; SARS-CoV-2; Mutations; Nucleocapsid Phosphoprotein (N); Infectious diseases; India